منهج الإمام الصالحي في نقد الأحاديث من خلال كتابه سبل الهدى و الرشاد في سيرة خير العباد - القوي زياد عبد السلام عبد (Al-Qurtas, 2025)
منهج الإمام الصالحي في نقد الأحاديث من خلال كتابه سبل الهدى و الرشاد في سيرة خير العباد